Correlating SAXS analysis with LSPR behavior: Poly(vinyl alcohol)-stabilized Ag nanoparticles - Singh M.; Sinha I.; Singh A.K.; Mandal R.K. (My University, 2025)
We explore the localized surface plasmon resonance (LSPR) behavior of aqueous sols of PVAstabilized AgNPs synthesized in presence of glucose as a reducing agent. The in situ synthesis parameters are tuned by adding increasing amounts of NaOH, which causes interesting variations in pH, LSPR curve broadening, and the evolution of AgNPs embedded PVA cross-linked nanostructures. Small angle X-ray scattering (SAXS) analysis is used to investigate sol aggregate characteristics. In all samples, mass fractal aggregates of two radius of gyration are formed. Assuming spherical form, the SAXS nanoparticle size distribution predicts a range from 6 to 60 nm. However, only the fractal aggregate features closely correspond to the observed LSPR characteristics. © Springer Science+Business Media B.V. 2011.